Methodological provisions for assessing economic and environmental damage to the resort and tourist and recreational industries caused by the Russian war against Ukraine - Petrushenko, M.M.; Semenov, O.S. (Економічний вісник Донбасу, 2025)
As a result of the study, methodological provisions were developed for assessing the economic and environmental damage caused to the resort and tourism and recreation sectors of Ukraine caused by Russian armed aggression during 2022–2025. The study integrates the provisions of national and international regulatory documents regulating the procedure for determining damage, assessing the ecological and economic consequences of military actions, and monitoring the state of natural, in particular, medical resources within health and recreation areas and tourist facilities. A comprehensive approach to assessing the economic and environmental damage to the resort and tourism and recreation sectors as a result of the Russian war against Ukraine was substantiated; the proposed procedure combines a rigorous quantitative basis (RCM, DLM, ESV) with qualitative procedures (expert assessments, scenarios, social surveys), which corresponds to international practices of UNEP, RDNA, SEEA, and OECD. Practical orientation of the obtained results: methodological provisions are consistent with the approaches used to assess damage to resorts, tourism and the environment in international practice; the proposed assessment approaches are universal in nature and can be used: in state recovery programs - for planning measures for the reconstruction of resort regions and the restoration of the recreational / health environment and individual natural, in particular, medical resources, primarily within the framework of the Plan of Ukraine for the Ukraine Facility; for the formation of requests for compensation for damage - when preparing reports to international organizations; for investment analysis - determining the potential for recovery and return on investment in the resort and tourism and recreation industries in the post-war period; for scientific purposes - creating a database of damages, predicting the consequences of potential aggressive anthropogenic activity. У результаті проведеного дослідження розроблено методологічні положення щодо оцінювання економіко-екологічних збитків, завданих курортній та туристично-рекреаційній галузям України, спричинених російською збройною агресією протягом 2022–2025 рр. У дослідженні інтегровано положення національних і міжнародних нормативних документів, що регламентують порядок визначення шкоди, оцінку еколого-економічних наслідків воєнних дій і моніторинг стану природних зокрема лікувальних ресурсів у межах оздоровчо-рекреаційних територій і туристичних об’єктів. Обґрунтовано комплексний підхід до оцінювання економіко-екологічних збитків курортній і туристично-рекреаційній галузям унаслідок російської війни проти України; запропонований порядок поєднує жорстку кількісну базу (RCM, DLM, ESV) із якісними процедурами (експертні оцінки, сценарії, соціальні опитування), що відповідає міжнародним практикам UNEP, RDNA, SEEA та OECD. Практична спрямованість отриманих результатів: методологічні положення узгоджуються з підходами, які застосовувалися для оцінювання збитків курортам, туризму та довкіллю в міжнародній практиці; запропоновані підходи оцінювання мають універсальний характер і можуть бути використані: в державних програмах відновлення – для планування заходів із реконструкції курортних регіонів і відновлення рекреаційного / оздоровчого середовища та окремих природних, зокрема лікувальних ресурсів, передусім у межах Плану України для Ukraine Facility; для формування запитів на компенсації збитків – при підготовці звітів до міжнародних організацій; для інвестиційного аналізу – визначення потенціалу відновлення та окупності вкладень у курортну і туристично-рекреаційну галузі в післявоєнний період; для наукових цілей – створення бази даних збитків, прогнозування наслідків потенційної агресивної антропогенної діяльності.